Penjatuhan Pidana Mati bagi Koruptor di Indonesia dalam Perspektif Utilitarianisme (Komisi Pemberantasan Korupsi, 2022)
Controversy regarding the death penalty in Indonesia is never-ending, particularly with regard to its application for crimes of corruption. This study offers a reflective analysis based on a utilitarian paradigm, which sees beneficiaries as a justification for the enactment of the law. Utilitarianism is used as an analytical tool because corruption is directly linked to state finances, meaning that legal sanctions must be enacted to ensure public benefit. The result of this study shows that the benefit generated by enacting the death penalty is unimpactful, whilst the costs are high, meaning that the imposition of the death penalty for corruptors is not proportionate according to a utilitarian perspective and a cost and benefit analysis.